Exploring new features for the (2+1)-dimensional Kundu–Mukherjee–Naskar equation via the techniques of ($$G^{\prime }/G,1/G$$)-expansion and exponential rational function - Yue, Xiao-Guang; Kaplan, Melike; Kaabar, Mohammed K. A.; Yang, Hongmei (Springer Science and Business Media LLC, 2022)
The aim of the manuscript is to study new optical soliton solutions of the Kundu-Mukherjee-Naskar (KMN) equation via the (G ` /G, 1/G )-expansion technique and the exponential rational function (ERF) procedure. The results are produced under the constraint conditions, and their graphical representation highlights them. These discoveries might aid in the comprehension of intricate nonlinear phenomena and oceanography. Studying the investigated equation in this paper is very important in explaining oceanographic phenomena such as rogue waves' ocean currents.
Keywords: QC Physics; QA Mathematics